Les Perforations D’ulcere Gastro-Duodenal Au Centre National Hospitalier Et Universitaire (Cnhu) De Cotonou (Benin) - Kc, Vignon; Dk, Mehinto; Kr, Vignon; Rii, Mbele; Nh, Natta N’tcha; Ej, Hounkpe (European Scientific Journal, ESJ, 2016)
Introduction: Duodenal or gastric ulcer perforations constitute a medical and surgical emergency. Purpose: Expose its epidemiological, diagnostic and therapeutic aspects. Method: About a retrospective study from January 1st 2006 to March 31st, 2012 in visceral surgery at CNHU of Cotonou, records of 86 cases of duodenal or gastric ulcer perforation were analyzed. Results: On average 13.8 cases / year, perforation of peptic ulcer was the most etiological cause of acute generalized peritonitis (25.7%). The average age was 34.2 years, the sex ratio of 16.2. Average admission stay was 6 days and it was observed: undocumented epigastralgia (42cas; 48.8%), no pathological medical history (32 cases; 37.2%). Peritoneal syndrome was in 81 cases (94.2%). Abdomen radiography without preparation (71 patients / 86; 82.6%) showed a pneumoperitoneum (52 cases / 71; 77.6%). The treatment was nonoperative (2 cases / 86; 2.3%) with a favorable outcome. Surgical patients had duodenal perforation (49 cases / 84; 57%), gastric perforation (35 cases / 84; 43%). Suturing with or without other technical devices was achieved in all cases. Postoperative complications were present in 28.5% of cases and parietal abscesses were documented as a priority (14 cases / 84; 16.7%). Mortality rate was 4.7% (4/86) and the average hospital stay was 11.6 days. Conclusion: The perforations of peptic ulcer were common in young men. Clinical examination was especially helpful in the diagnosis by abdomen radiography without preparation. The treatment was medical and surgical and the outcome was mostly favorable.